Lung Ultrasound in Pediatric Acute Respiratory Distress Syndrome Received Extracorporeal Membrane Oxygenation: A Prospective Cohort Study - Zhang, Yucai; Wang, Chunxia; Wang, Fei; Shi, Jingyi; Dou, Jiaying; Shan, Yijun; Sun, Ting; Zhou, Yiping (Frontiers in Pediatrics, 2022)
Background: The aim of this study was to assess the prognostic value of the lung ultrasound (LUS) score in pediatric acute respiratory distress syndrome (pARDS) received extracorporeal membrane oxygenation (ECMO). Methods: A prospective cohort study was conducted in pediatric intensive care unit (PICU) of a tertiary hospital from January 2016 to June 2021. The pARDS patients received ECMO support were enrolled in this study. LUS score was measured at initiation of ECMO (LUS-0h), then at 24 (LUS-24h), 48 (LUS-48h), 72 hours (LUS-72h) after ECMO, and when weaned from ECMO (LUS-wean). The value of LUS scores at the first 3 days of ECMO as a prognostic predictor were analyzed. Results: Twenty-nine children with pARDS received ECMO were enrolled with median age of 26 (IQR 9, 79) months. The median duration of ECMO support was 162 (IQR 86, 273) hours and the PICU mortality was 31.0 % (9/29). The values of LUS-72h and LUS-wean were significantly lower in survivors than that in non- survivors (both P< 0.001). Daily fluid balance volume during the first 3 days of ECMO were strongly correlated with LUS score [1st day: r=0.460, P=0.014; 2nd day: r=0.540, P=0.003; 3rd day: r=0.589, P=0.001]. The AUC of LUS-72h for predicting PICU mortality in these patients was 1.000, and the cutoff value of LUS-72h was 24 with a sensitivity of 100.0% and a specificity of 100.0%). Furthermore, patients were stratified in two groups of LUS-72h≥24 and LUS-72h<24. Consistently, PICU mortality, length of PICU stay, ratio of shock, VIS value, and need continuous renal replacement therapy (CRRT) were significantly higher in group of LUS-72h≥24 than in group of LUS-72h<24 (all P < 0.05). Conclusions: LUS score is a promising tool for predicting the prognosis in patients with ARDS under ECMO support. Moreover, LUS-72h≥24 is associated with high risk of PICU mortality in pARDS on ECMO.